CLASSIFICATION OF TATTOOS AND TATTOO REMOVAL - Ashurov Dilshod Davlatovich (Web of Journals Publishing, 2025)
Tattooing is an ancient procedure and has been identified in different societies for centuries. Tattooing is a process where exogenous pigments are introduced into the dermis and epidermis. Tattoos consist of thousands of particles of tattoo pigment suspended in the skin. While normal human growth and healing processes will remove small foreign particles from the skin, tattoo pigment particles are permanent because they are too big to be removed.